Hydroxyl fluoroalkyl aromatic hydrocarbon derivative modified binder as well as preparation method and application thereof

By using adhesives modified with hydroxytrifluoroalkyl aromatic derivatives, the shortcomings of existing lithium-ion battery adhesives in terms of adhesion, wear resistance and low temperature resistance are solved, and higher chemical stability and thermal stability are achieved, and battery performance is improved.

CN119552292AActive Publication Date: 2025-03-04WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411668458.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-04
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The bonding strength, wear resistance and low temperature resistance of existing lithium-ion battery adhesives are limited, making it difficult to meet the requirements of chemical stability and thermal stability during battery circulation.

Method used

A binder modified with hydroxytrifluoroalkylaromatic derivatives contains lipophilic and hydrophilic groups and branched structures, and is prepared by initiator cross-linking and neutralization reaction to form a polymer with excellent adhesive strength.

Benefits of technology

The bonding force between the negative electrode materials is significantly improved, the strength of the slurry and the force between the current collector is enhanced, and the battery performance is improved, especially in high energy density and wide temperature ranges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a hydroxyl fluoroalkyl aromatic hydrocarbon derivative modified binder as well as a preparation method and application thereof. The binder is prepared by crosslinking acrylic acid, epoxy chloropropane and p-hydroxyl trifluoroalkyl styrene. The hydrophilic group trifluoroalkyl group and the hydrophilic group hydroxyl group (which can form a hydrogen bond between slurry) in the binder enable the polymer to regulate and control the hydrophilic and hydrophobic properties of the slurry, so that the bonding force between the binder and an active material can be remarkably improved. The branched chains of the binder enhance the structural stability of molecules and increase the viscosity and suspension property of the slurry, so that the electrode structure becomes more stable when the binder is applied to the negative electrode of the lithium battery as the binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a binder modified by a hydroxyfluoroalkyl aromatic derivative, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the characteristics of high energy density, long cycle life, flexible size design, clean and pollution-free, and are widely used in new energy vehicles, energy storage equipment, consumer electronics and other fields. They are one of the most competitive chemical batteries at present.

[0003] With the continuous development of the lithium-ion battery industry, the performance requirements for binders are also constantly increasing. Binders are key auxiliary materials for lithium-ion batteries, and their usage accounts for 5% to 8% of the positive and negative active materials. The main function is to connect the active material, the conductive agent and the current collector, so that the active material, the conductive agent and the current collector are connected. During the charge and discharge process, it can provide sufficient bonding strength to ensure that the active material will not fall off and fail during the battery production and use (storage, circulation).

[0004] At present, the widely used binders are mainly polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC). In addition, water-based binders such as polyacrylic acid (PAA), polyacrylonitrile (PAN) and polyacrylate also occupy a certain market. The above binders have limited bonding strength, wear resistance and low temperature resistance, which need to be further improved to improve their chemical stability and thermal stability during battery cycling.

[0005] The application of lithium-ion batteries is constantly developing towards high energy density, high output, and adaptability to a wider range of temperature requirements. Therefore, it is urgent to develop a binder with better performance. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing a hydroxytrifluoroalkyl aromatic hydrocarbon modified binder, wherein the hydroxytrifluoroalkyl aromatic hydrocarbon modified binder contains lipophilic and hydrophilic groups and a branched structure, so that it has excellent adhesion.

[0007] Another object of the present invention is to provide such a hydroxytrifluoroalkyl aromatic hydrocarbon modified binder and its application.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] A method for preparing a binder modified by a hydroxytrifluoroalkyl aromatic derivative comprises the following steps:

[0010] 1) cross-linking a carboxyl group-containing monomer A, an epichlorohydrin monomer B and a hydroxyl group-containing trifluoroalkyl aromatic monomer C under the action of an initiator to prepare a first mixed solution;

[0011] 2) subjecting the first mixed solution to a neutralization reaction under the action of a neutralizing agent, adjusting the pH value and the content of non-volatile matter, and finally obtaining the binder.

[0012] In a specific embodiment, the carboxyl group-containing monomer A comprises one or more of acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic acid and fumaric acid, preferably acrylic acid.

[0013] In a specific embodiment, the hydroxyl fluoroalkyl aromatic hydrocarbon monomer C comprises one or more of p-hydroxytrifluoroalkylstyrene, o-hydroxytrifluoroalkylstyrene, p-hydroxytrifluoroalkylphenyl acrylate and p-hydroxytrifluoroalkylphenyl methacrylate, preferably p-hydroxytrifluoroalkylstyrene.

[0014] In a specific embodiment, based on the total mass of all monomers, the amount of the carboxyl-containing monomer A added is 10-30wt%, for example, 15wt%, 17wt%, 20wt%, 23wt%, 25wt%, 28wt%, etc., the amount of the epichlorohydrin monomer B added is 20-40wt%, for example, 20wt%, 23wt%, 25wt%, 28wt%, 30wt%, 35wt%, 37wt%, 39wt%, etc., and the amount of the hydroxyl-containing fluoroalkyl styrene monomer C added is 40-50wt%, for example, 41wt%, 43wt%, 45wt%, 46wt%, 48wt%, 49wt%, etc.

[0015] In a specific embodiment, the initiator is a thermal initiator and / or a redox initiator; preferably, the initiator is one or more of di-tert-butyl peroxide, ammonium sulfate, sodium persulfate, potassium persulfate, sodium pyrosulfite and sodium bisulfite.

[0016] In a specific embodiment, the process comprises mixing carboxyl-containing monomer A, epichlorohydrin monomer B, hydroxyl-containing trifluoroalkyl aromatic monomer C and water, and performing polymerization reaction under the catalytic action of an aqueous solution of an initiator to obtain a first mixed solution.

[0017] In a specific embodiment, the mass ratio of all monomers and initiators is (100-2000):(1-15), for example, 100:1, 1200:10, 2000:15, 100:15, 2000:1, 1500:5, etc.

[0018] In a specific embodiment, the initiator aqueous solution is added dropwise; the addition time is 1-2h, such as 1.1h, 1.3h, 1.5h, 1.6h, 1.8h, 1.9h, etc., and the reaction temperature during the addition is 30-70°C, such as 40°C, 50°C, 60°C, 65°C, etc. There is no particular restriction on the concentration of the initiator aqueous solution, as long as the initiator is dissolved in an appropriate amount of water to prepare a solution for easy addition.

[0019] In a specific embodiment, in step 2), the temperature of the first mixed solution is raised to 50-90°C, such as 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 82°C, 85°C, 90°C, etc. before neutralization.

[0020] In a specific embodiment, the neutralizing agent is an inorganic alkali metal compound, preferably one or more of sodium carbonate, sodium hydroxide, potassium carbonate, potassium hydroxide, lithium carbonate, and lithium hydroxide; preferably, the pH value of the solution after neutralization is 6-9, for example, 7 or 8.

[0021] In a specific embodiment, the pH value and the content of non-volatile matter are adjusted, and the solution temperature is lowered to 20-25° C. after neutralization to finally obtain the modified binder, wherein the solid content of the modified binder is 2-10wt%, for example, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, etc.; the number average molecular weight of the modified binder is 400,000-500,000, for example, 410,000, 420,000, 430,000, 440,000, 450,000, 460,000, 470,000, 480,000, 490,000, 500,000, etc.

[0022] On the other hand, the binder modified with a hydroxytrifluoroalkyl aromatic hydrocarbon derivative prepared by the aforementioned preparation method.

[0023] On the other hand, the binder modified with a hydroxytrifluoroalkyl aromatic derivative prepared by the aforementioned preparation method or the aforementioned modified binder is used in a negative electrode of a lithium ion battery. Preferably, the modified binder accounts for 0.3 to 2 wt% of the total dry powder slurry and is used in a negative electrode of a lithium ion battery.

[0024] Compared with the prior art, the modified binder of the present invention has the following beneficial effects:

[0025] The hydroxyfluoroalkyl aromatic modified binder provided by the present invention is a styrene derivative containing a hydroxyfluoroalkyl group, wherein the fluoroalkyl group is a lipophilic group and the hydroxyl group is a hydrophilic group, so that the polymer regulates the hydrophilicity and hydrophobicity of the slurry. In the preparation of the slurry, a strong intermolecular force is formed between the active material (graphite, silicon carbon, silicon, etc.) and the conductive agent, which can significantly improve the adhesion between the negative electrode materials. At the same time, the binder contains abundant carboxyl, hydroxyl and carboxylate groups, which not only enhances the strength of the slurry itself, but also improves the interaction between the slurry and the current collector. Epichlorohydrin mainly plays the role of connecting small molecule monomer A and macromolecular monomer C. The side chains on the binder molecular chain make the structure of the binder more stable, and also leave more space for the molecules after winding to make the negative electrode smoother in the process of lithium insertion / delithiation, thereby improving the battery performance. DETAILED DESCRIPTION

[0026] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.

[0027] The main sources of raw materials involved in the following examples are as follows Table 1:

[0028]

[0029]

[0030] Unless otherwise specified, other chemical reagents used in the examples were purchased from the market and were of analytical grade.

[0031] Example 1

[0032] (1) Add 1.2 kg of deionized water to a 3 L round-bottom flask and heat to 50 °C;

[0033] (2) 60 g of acrylic acid, 40 g of epichlorohydrin, 100 g of p-hydroxytrifluoromethylstyrene and 200 g of water were mixed and stirred until dissolved;

[0034] (3) Pass nitrogen for half an hour until the oxygen content of the solution drops below 5% to avoid the inhibitory effect of oxygen on the early stage of the reaction;

[0035] (4) preparing an aqueous solution of ammonium peroxydisulfate (0.3 g ammonium peroxydisulfate dissolved in 25 g deionized water) and an aqueous solution of sodium pyrosulfite (0.2 g ammonium peroxydisulfate dissolved in 25 g deionized water);

[0036] (5) The solutions prepared in step (2) and step (4) were simultaneously added dropwise to the round-bottom flask for 1 h;

[0037] (6) After the addition is completed, the temperature is raised to 70° C., and a sodium carbonate aqueous solution is added to adjust the pH of the solution to 7.0. After the neutralization is completed, the temperature is lowered to 25° C. and the solid content of the solution is adjusted to 5 wt % to obtain the target modified binder.

[0038] Example 2

[0039] The method is similar to that of Example 1, except that the types and amounts of the three monomers are 50 g of crotonic acid, 60 g of epichlorohydrin, and 90 g of p-hydroxytrifluoromethylstyrene, respectively; the polymerization reaction dropwise addition time is 2 h; and the pH is adjusted to 9.

[0040] Example 3

[0041] The method is similar to that of Example 1, except that the types and amounts of the two monomers are 20 g of maleic acid and 80 g of epichlorohydrin, respectively, and the initiator adopts a thermal initiation system (ammonium persulfate aqueous solution, 0.3 g dissolved in 25 g of deionized water). The reaction temperature is increased to 70°C, and the target binder solid content is adjusted to 10 wt%.

[0042] Example 4

[0043] The method is similar to that of Example 1, except that the types and amounts of the three monomers are 60 g acrylic acid, 60 g epichlorohydrin, and 80 g p-hydroxytrifluoroalkylstyrene, respectively; the initiator is adjusted to an aqueous solution of ammonium persulfate (0.9 g ammonium persulfate dissolved in 25 g deionized water) and an aqueous solution of sodium pyrosulfite (0.6 g ammonium persulfate dissolved in 25 g deionized water); the neutralization temperature is increased to 90° C., and sodium hydroxide is used as the neutralizer.

[0044] Comparative Example 1

[0045] Similar to the method of Example 1, monomer B is adjusted to vinyl chloride.

[0046] Comparative Example 2

[0047] Similar to the method of Example 1, the monomer C is adjusted to styrene.

[0048] Test Method

[0049] The binder prepared by the above method is applied to the negative electrode of the lithium battery, and the steps are as follows:

[0050] First, according to the formula of negative electrode active material graphite: conductive carbon black sp: thickener CMC: binder = 97.0:1.2:0.3:1.5, CMC was added to 120 parts of deionized water, stirred at high speed for 15 minutes, and then sp, graphite and binder were added in turn. After each material was added, it was necessary to stir at high speed for 15 minutes to ensure mixing, and then sieved through a 200-mesh nylon filter to obtain the negative electrode slurry. Then the coating operation was carried out, and the prepared negative electrode slurry was evenly coated on the current collector (copper foil) using a coating machine, with a coating thickness of 100μm, and then dried in an oven at 110℃ for 5 minutes. After rolling three times with a roller press at room temperature, a negative electrode sheet with a thickness of 70μm was obtained. Finally, a cutter was used to cut the sheet into 200mm long and 20mm wide sheets for peel strength testing.

[0051] Peel strength evaluation: Use Kejian tensile testing machine to test the peel strength of the cut pole piece. The specific operation is as follows: In a constant temperature and humidity room, fix the cut pole piece on a smooth and clean stainless steel plate with 150mm and 20mm wide 3M double-sided tape, and then fix the steel plate on the base of the tensile machine. The copper foil without tape is clamped with the tensile machine probe, and then the base of the tensile machine pulls the pole piece at a speed of 5cm / min. The sensor measures the peel force during the whole process. Take 5 parallel samples in each group and get the average value, which is the final peel strength. Peel force = computer indication / 0.015, unit is N / m.

[0052] Product viscosity test: Use Brookfield DV2T viscosity tester, 64# rotor, 12rpm conditions for testing, product constant temperature (25±0.5℃), rotor groove and liquid surface level, read after the reading is stable (no climbing phenomenon), if there is climbing phenomenon, record the data before climbing, each sample is tested 3 times and the average value is taken.

[0053] Slurry stability test: Leave the prepared slurry at room temperature for 5 days, test the solid content at the top and bottom of the slurry, observe the stratification of the slurry, and judge the stability of the slurry.

[0054] The application performance tests of the modified binders of the embodiments and comparative examples in the negative electrode plates of lithium batteries are as follows:

[0055]

[0056] From the results in the table, it can be seen that Examples 1-4 exhibit excellent viscosity and excellent bonding strength due to the presence of hydroxyl, trifluoromethyl and side chains. Comparative Example 1 reduces the amount of hydroxyl contained in the polymer, and Comparative Example 2 eliminates trifluoromethyl and side chains. Both operations reduce the viscosity of the adhesive, and the peeling strength performance is also very poor. From the perspective of slurry preparation, the slurry dispersibility of Examples 1-4 and Comparative Example 1-2 is normal, but after three days of static storage, the upper and lower layers of Comparative Example 1-2 have obvious differences in solid content, and the appearance is stratified, with poor stability. The presence of hydroxyl and trifluoromethyl in Example 1-4 has a strong ability to regulate the hydrophilicity and hydrophobicity of the slurry, forming an effective hydrophobic association and enhancing the suspension of the slurry.

[0057] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a binder modified with a hydroxytrifluoroalkyl aromatic derivative, characterized in that: The following steps are involved: 1) cross-linking a carboxyl group-containing monomer A, an epichlorohydrin monomer B and a hydroxyl group-containing trifluoroalkyl aromatic monomer C under the action of an initiator to prepare a first mixed solution; 2) subjecting the first mixed solution to a neutralization reaction under the action of a neutralizing agent, adjusting the pH value and the content of non-volatile matter, and finally obtaining the binder.

2. The preparation method according to claim 1, characterized in that: The carboxyl group-containing monomer A comprises one or more of acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic acid and fumaric acid, preferably acrylic acid.

3. The preparation method according to claim 1, characterized in that: The hydroxyl-containing fluoroalkyl aromatic monomer C comprises one or more of p-hydroxytrifluoroalkylstyrene, o-hydroxytrifluoroalkylstyrene, p-hydroxytrifluoroalkylphenyl acrylate and p-hydroxytrifluoroalkylphenyl methacrylate, preferably p-hydroxytrifluoroalkylstyrene.

4. The preparation method according to any one of claims 1 to 3, characterized in that: Based on the total weight of all monomers, the added amount of the carboxyl group-containing monomer A accounts for 10-30wt%, the added amount of the epichlorohydrin monomer B accounts for 20-40wt%, and the added amount of the hydroxyl-containing fluoroalkyl styrene monomer C accounts for 40-50wt%.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The initiator is a thermal initiator and / or an oxidation-reduction initiator; preferably, the initiator is one or more of di-tert-butyl peroxide, ammonium sulfate, sodium persulfate, potassium persulfate, sodium pyrosulfite and sodium bisulfite.

6. The preparation method according to claim 1, characterized in that: The method comprises mixing carboxyl-containing monomer A, epichlorohydrin monomer B, hydroxyl-containing trifluoroalkyl aromatic monomer C and water, and performing polymerization reaction under the catalytic action of aqueous solution of initiator to obtain a first mixed solution.

7. The preparation method according to claim 6, characterized in that: The mass ratio of all monomers and initiators is (100-2000):(1-15); Preferably, the aqueous initiator solution is added dropwise; More preferably, the dropping time is 1-2 hours, and the reaction temperature during the dropping is 30-70°C.

8. The preparation method according to claim 1, characterized in that: In step 2), the temperature of the first mixed solution is raised to 50-90° C. before neutralization; Preferably, the neutralizing agent is an inorganic alkali metal compound, preferably one or more of sodium carbonate, sodium hydroxide, potassium carbonate, potassium hydroxide, lithium carbonate, and lithium hydroxide; More preferably, the pH value of the solution after neutralization is 6-9; and / or The solid content of the modified binder is 2-10wt%.

9. A binder modified with a hydroxytrifluoroalkyl aromatic hydrocarbon derivative prepared by the preparation method according to any one of claims 1 to 8.

10. Use of a binder modified with a hydroxytrifluoroalkyl aromatic derivative prepared by the preparation method according to any one of claims 1 to 8 or a modified binder according to claim 9 in a negative electrode of a lithium ion battery, preferably, the modified binder accounts for 0.3 to 2 wt% of the total dry powder slurry for a negative electrode of a lithium ion battery.

Citation Information

Patent Citations

  • Preparation method and application of solution type binder

    CN117567970A

  • Aqueous binder for negative electrode of lithium ion battery and the preparation method thereof

    KR1020170097577A